2018
DOI: 10.3987/com-18-s(t)20
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of Oligonucleotides Containing 3′-O,4′-C-Ethyleneoxy-Bridged 5-Methyluridines

Abstract: -A phosphoramidite of 3ʹ-O,4ʹ-C-ethyleneoxy-bridged 5-methyluridine (3ʹ,4ʹ-EoNA-T) was successfully incorporated into oligonucleotides, and their abilities to form duplexes with RNA and DNA as well as triplexes with double-stranded DNA were evaluated. The stabilities of the duplexes formed between RNA and 3ʹ,4ʹ-EoNA-modified oligonucleotides were only slightly lower than those of the natural DNA-RNA duplex, while the duplexes formed between 3ʹ,4ʹ-EoNA-modified oligonucleotides and DNA were drastically less sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…We have previously developed several 3′,4′-bridged nucleic acids (3′,4′-BNAs, Figure ). The sugar conformation of all 3′,4′-BNAs and trans -3′,4′-BNAs is an S-type. Shaikh et al developed a bicyclic 2′-deoxyribonucleoside with a 3′,4′-bridge structure, and X-ray crystal structural analysis revealed that the sugar conformation of the nucleoside was, interestingly, an N-type .…”
Section: Introductionmentioning
confidence: 99%
“…We have previously developed several 3′,4′-bridged nucleic acids (3′,4′-BNAs, Figure ). The sugar conformation of all 3′,4′-BNAs and trans -3′,4′-BNAs is an S-type. Shaikh et al developed a bicyclic 2′-deoxyribonucleoside with a 3′,4′-bridge structure, and X-ray crystal structural analysis revealed that the sugar conformation of the nucleoside was, interestingly, an N-type .…”
Section: Introductionmentioning
confidence: 99%